The Coronavirus pandemic as a game-changer: When NBA players forced America to think. again - Galily, Y. (Frontiers in Psychology, 2021)
On August 26, 2020, some of the best-known athletes in the world decided to act. Players from the National Basketball Association's Milwaukee Bucks did not arrive for their playoff game against the Orlando Magic and the league was forced to cancel the match. The Bucks refused to play the fifth game of the series in protest against the firing of an unarmed black man, Jacob Blake, in Kenosha, Wisconsin, only few miles from where they usually play. Many teams in other American leagues followed the Bucks and Magic. Players from all NBA teams held emergency meetings, during which players requested to end the season immediately.